Food Procurement Strategy During the Low Season at the Como Uma Ubud Hotel - Ni Kadek Meira Yanti Yanti; I Dewa Ayu Rai Sumariati; Luh Nyoman Tri Lilasari (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze food procurement strategies during the low season at Hotel COMO Uma Ubud. The low season is a period of low occupancy rates, which leads to a decrease in food demand, thereby increasing the risk of stockpiling and spoilage in the warehouse. This study uses a qualitative descriptive method with data collection techniques including interviews, observation, and documentation. The results of the study indicate that the FIFO method applied has not been effective during the low season because it causes food ingredients to be left unused, leading to spoilage and waste. As a solution, the hotel has begun to implement the Just in Time (JIT) method, which involves procuring food ingredients in small quantities and according to need, to avoid excess stock. This strategy has proven effective in reducing the risk that accours, improving cost efficiency, and maintaining the food procurement. The Strategy of JIT also reflects coordination between internal departments and collaboration with local suppliers. Thus, the JIT-based procurement strategy is an appropriate solution for efficiently managing food supplies during the low season, while supporting sustainability and customer satisfaction.